Product-led growth companies find a new way to serve customers companies from Zoom to Slack lean on the product itself to find customers, convert them to paying, and drive rapid expansion, without adding customer-facing staff - Libert, Barry; Davenport, Thomas H. 1954- (MIT Sloan Management Review, 2022)
Many companies are embedding processes like providing recommendations, taking orders, upselling and delivering services, with minimal customer contact. Key features of this approach, called product-led growth, or PLG, include free or very low-cost introductory pricing, with higher prices for more functionality (like what's offered by Zoom) and overall ease of use. The authors discuss successful PLG strategies and PLG's potential for both software and non technology firms.